The revelation of God - Congard, Marie Joseph, 1904 (London, Darton, Longman and Todd : New York, Herder and Herder, 1968)
"This book together with Faith and spiritual life was first published as Les voices du Dieu vivant..."
Includes bibliogrpahical references
Keywords: Revelation